THE STANDPOINT OF PRIVATE ISLAMIC COLLEGE STUDENTS TOWARD ENGLISH-SPEAKING MATERIAL: A NEED ANALYSIS STUDY AT STIT TANGGAMUS - Pradana, Sandi (LinguaScopes: International Journal of Language Education, 2024)
This research aimed to understand the opinions of first-year students at STIT Tanggamus regarding the most suitable English-speaking material for their studies. Questionnaires were distributed to 20 respondents. The results showed that 60% of the students recognized the importance of speaking in daily conversations. 40% of them felt that they lacked proficiency in grammar and required more discussion activities to improve. Additionally, 50% of the students believed that music would be a valuable tool for learning to speak English. The findings indicate that STIT Tanggamus students have specific needs regarding English-speaking content. Therefore, the institution must provide appropriate materials and resources to address these needs. The research raises questions about the effectiveness of English-speaking material in enhancing students' language skills and the specific learning needs of STIT Tanggamus students regarding speaking skills.